Hyper-Personalization and the Privacy Paradox: An Opinion-Based Academic Perspective - Abdulwahab, Basel; Kumar T.P, Krishna (The Indonesian Institute of Science and Technology Research, 2025)
The rapid advancement of data-driven digital marketing has introduced unprecedented opportunities for hyper-personalization. This innovation allows marketers to tailor content and services to individual users in real time, enhancing engagement and customer satisfaction. However, the rise of hyper-personalization is accompanied by growing concerns regarding user data protection, commonly described as the privacy paradox. This paradox reflects the tension between consumers’ desire for personalized experiences and their apprehension about potential data misuse. This article provides an opinion-based discussion that analyzes the psychological implications of this phenomenon, highlighting how consumer trust, decision-making, and long-term loyalty may be affected. In doing so, the paper emphasizes the importance of balancing marketing effectiveness with ethical data practices. The article concludes with practical considerations for marketers navigating this dilemma, suggesting approaches that align personalization strategies with both consumer expectations and evolving standards of digital responsibility.